Eve of destruction : the coming age of preventive war - Nichols, Thomas M., 1960- (University of Pennsylvania Press, 2008)
In an age of new threats to international security, the old rules of war are rapidly being discarded by the great powers. This study explores how and why states will exercise the preventive use of force in the twenty-first century, and how this violence might be contained and controlled.